2021
DOI: 10.3389/fnagi.2021.645611
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in COVID-19 Patients With New Neurological Manifestations: A Retrospective Cohort Study in a Romanian Neurology Department

Abstract: Introduction: The emerging Coronavirus Disease (COVID-19) pandemic caused by Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a serious public health issue due to its rapid spreading, high mortality rate and lack of specific treatment. Given its unpredictable clinical course, risk assessment, and stratification for severity of COVID-19 are required. Apart from serving as admission criteria, prognostic factors might guide future therapeutic strategies.Aim: We aimed to compare clinical features an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, Paranga et al concluded that the best role for CRP as a biomarker was to distinguish between severe and non-severe cases [ 61 ]. CRP levels were also associated with new neurological manifestations in elder patients [ 62 ] and children with pediatric inflammatory multisystem syndrome (PIMS) [ 41 , 63 ]. In the rare cases of vertical transmission, such as the one identified by Iacob and his team, CRP was elevated in the newborns with positive SARS-CoV-2 PCR testing [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Paranga et al concluded that the best role for CRP as a biomarker was to distinguish between severe and non-severe cases [ 61 ]. CRP levels were also associated with new neurological manifestations in elder patients [ 62 ] and children with pediatric inflammatory multisystem syndrome (PIMS) [ 41 , 63 ]. In the rare cases of vertical transmission, such as the one identified by Iacob and his team, CRP was elevated in the newborns with positive SARS-CoV-2 PCR testing [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The major laboratory markers that were studied by Romanian authors are displayed in Table 1. Yes, even more so in Roma [53,54,[58][59][60][61][62]70] Diabetes [48,94] Antiphospholipid syndrome [47] Hypertension [27] Cardiac dysfunction [46,73,93] Overweight/metabolic syndrome [27,54,93] Lung involvement [50,57] PIMS [83] Chronic Spontaneous Urticaria Exacerbation [42] Pneumothorax/ pneumomediastinum [31,72] Liver failure [44] Multiple organ dysfunction [ [57,58,102,103] No [55] More comorbidities [29,101] Lung involvement [57] In addition, this article aimed to identify gaps in this research and provide encouragement for Romanian research to focus on novel and detailed aspects of the pandemic. For instance, as Romania grapples with the aftermath of the COVID-19 pandemic, understanding the long-term effects of the disease is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that studies that cite higher frequency of headache are often using healthcare professionals as their population, and therefore these individuals may be better able to recognize their symptoms. Davidescu et al described in their retrospective cohort study that the most frequent neurological manifestation of COVID-19 in younger patients was headache, in contrast to stroke and confusion in older adults [ 10 ].…”
Section: Prevalencementioning
confidence: 99%
“…Moreover, it was established that reducing IL-6 levels is correlated with the amelioration of olfaction and taste dysfunction in COVID-19 [26]. Additionally, in stroke, as in other neurological manifestations, the neutrophillymphocyte ratio [116], C reactive protein [130] and serum ferritin are increased in a large proportion of patients with COVID-19 [8,39]. Severe hypoxia, characteristic in many COVID-19 patients, can induce cerebrovascular dilation, oedema and ischemia [125].…”
Section: Neuro-inflammationmentioning
confidence: 99%